Gestión de ventas de la Empresa Artefacta de la parroquia Ricaurte, periodo 2023. - Contreras Molina, Jhomayra Carolina (2024)
This study focuses on the sales management of the company Artefacta in the parish of Ricaurte during 2023, addressing strategic challenges and their impact on finances and customer satisfaction. It arises from the need to optimize economic growth in the face of market competitiveness, using research techniques to evaluate marketing strategies and staff effectiveness. The general objective is to analyze sales management to evaluate its influence on economic growth, using interviews and surveys as the main methodological techniques. The results highlight the implementation of creative and disruptive marketing strategies, although they point out areas for improvement in personalization and communication of product information. Customer satisfaction, which is generally positive, suggests the need to increase consistency and accuracy in the information provided. A focus on personalization, clarity in product communication, and a sales strategy that adapts to market needs is recommended. This analysis reinforces the importance of well-executed strategies that resonate with customers and underscores the opportunity to improve sales management to drive customer loyalty and retention.